Statistical yearbook for Asia and the Far East - United Nations Economic Commission for Asia and the Far East. (Bangkok ECAFE, 1997)
Annual
Keywords: Asia -- Statistics -- Periodicals; East (Far East) -- Statistics -- Periodicals